A Quasi Experimental Study to Assess the Effectiveness of Ginger Powder on Dysmenorrhea among Nursing Students in Selected Nursing Colleges, Hoshiarpur, Punjab - *, Satyajit; Kaur, Ishmeet (International Journal of Innovative Research in Medical Science, 2017)
Background: primary dysmenorrhea is one of the most common gynecologic disorders affecting more than half of menstruating women that interferes with daily activities. Some studies have found alternative methods such as acupuncture, acupressure, stimulation, massage, aromatherapy and ginger to be fairly effective for treatment of dysmenorrhea. Ginger is a spice that has traditionally been treated as medicine. So, ginger powder was used to assess its effect on dysmenorrhea among nursing students. Material & Methods: sample of 60 nursing students from selected nursing colleges, 30 each in experimental group and control group were selected by non-probability purposive sampling technique. Subjective and objective assessment of level of dysmenorrhea wer done by using modified mcgill pain questionnaire and standardized wong bakers faces pain rating scale respectively. Analysis was done by using both descriptive and inferential statistics. Findings: findings showed that according to subjective assessment in experimental group, 100% nursing students had mild level of pain, whereas in control group, 46.67% had mild level of pain, On the other hand, according to objective assessment in experimental group 66.7% had mild level of pain whereas in control group 56.7% had moderate pain. Results were found statistically significant at p < 0.01 level in experimental group on both subjective and objective assessment. Conclusion: study reveals that there was impact of ginger powder on dysmenorrhea among nursing students in experimental group.